Ketogenic diet in psychiatry: application in treating depression among athletes - Kumięga, Paulina; Kudas, Zuzanna; Perchel, Nikola; Litwin, Aleksandra; Krzywicka, Karolina; Nowocin, Paweł; Wasiński, Piotr; Dąbrowska, Natalia; Koszyk, Martyna; Kulczyński, Dawid (Quality in Sport, 2025)
Depression is a prevalent mental health challenge, particularly in athletes, where the interplay of high-performance demands, physical stress, and injury exacerbates psychological vulnerabilities. Emerging evidence suggests that the ketogenic diet (KD), a high-fat, moderate-protein, and low-carbohydrate dietary intervention, holds therapeutic potential for managing depression. KD induces ketosis, a metabolic state that enhances brain energy metabolism, reduces neuroinflammation, and stabilizes neurotransmitter function, all of which are implicated in the pathophysiology of depression. This review synthesizes findings from recent clinical trials, meta-analyses, and case studies focusing on KD’s neurological and psychological effects. The results indicate significant improvements in depressive symptoms, mood stabilization, and mental resilience among individuals adhering to KD. Moreover, KD’s modulation of the gut-brain axis introduces an additional pathway for improving mental health by fostering a diverse gut microbiome and reducing systemic inflammation. For athletes, KD offers dual benefits: alleviating depressive symptoms while supporting cognitive function and recovery. However, adherence to the diet and potential side effects such as fatigue and gastrointestinal discomfort pose challenges. Current research is limited by a lack of large-scale, randomized controlled trials specifically targeting athletic populations. In conclusion, KD demonstrates promise as an adjunctive therapy for depression in athletes. Its multifaceted effects on brain health and performance metrics underscore its potential role in sports psychiatry. Further research is necessary to optimize KD protocols and establish evidence-based guidelines for its clinical application in athletic populations.